Jokes to tell your friends - Woodworth, Viki (St. Paul, MN : Child's World, 1996)
A collection of jokes that can be shared. Example: On what side of the house do trees grow? The outside!
7 - 9 years
Keywords: Wit and humor, Juvenile; Jokes